2010
DOI: 10.1186/1758-5996-2-60
|View full text |Cite
|
Sign up to set email alerts
|

Sudeck's disease stage 1, or diabetic Charcot's foot stage 0? Case report and assessment of the diagnostic value of MRI

Abstract: BackgroundThe diagnosis of Sudeck's syndrome stage 1 (nowadays termed complex regional pain syndrome I, abbreviated CRPS I) is based on clinical features, namely swelling and pain in a limb. Plain X-ray may be normal. In the absence of pain sensitivity, e.g. in diabetic neuropathy, CRPS I of the foot can be mistaken for Charcot's foot stage 0 (so-called neuro-osteoarthropathy).Case presentationThe case of a type-1 diabetic woman is reported, in whom CRPS I following a calcaneal fracture was mistaken for Charco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…(b) Contrary to earlier claims [38], EESC in the present study did not regress without fluctuation and migration in some cases. Temporary non-regression (or progression) of EESC was observed in the present study in about 1/3 of all FUS.…”
Section: Discussioncontrasting
confidence: 99%
“…(b) Contrary to earlier claims [38], EESC in the present study did not regress without fluctuation and migration in some cases. Temporary non-regression (or progression) of EESC was observed in the present study in about 1/3 of all FUS.…”
Section: Discussioncontrasting
confidence: 99%
“…[ 26 ] Depending upon the stage of disease, soft tissue edema(acute/subacute stage) and soft tissue atrophy (chronic stage) may be associated. [ 26 27 ] However, two important pitfalls should be kept in mind. In children and adolescents, patchy/reticular appearance of the marrow may be normally observed with patchy red marrow conversion.…”
Section: Category I Lesionsmentioning
confidence: 99%
“…Zampa et al measured contrast medium (gadolinium) uptake on dynamic MRIs in 40 patients with acute CN and found this to be a reliable means of monitoring the treatment outcome in the acute stage 41 . However, differentiating early Sudeck disease from the acute stage of CN is still a grey area 42 . In diabetic neuropathic feet, Thorning et al found areas of increased bone marrow edema in the midfoot and hindfoot, remote from the area shown to be affected by T2 weighted MRI 43 .…”
Section: Computerized Tomography and Magnetic Resonance Imagingmentioning
confidence: 99%